A note on religious participation and community involvement. Issue 4 (8th August 2019) - Theodori, Gene L.; Robinson, Chothiakadavil S.
ABSTRACT: Building upon previous research and incorporating a newly constructed measure of religious participation assessing both attendance at religious meetings and involvement in religious groups, we (re)examine the association between religious participation and community involvement using data collected in a 2012 survey of persons living in small and rural places in Texas. Substantial support was found for the hypothesis that increased levels of religious participation are associated with increased levels of involvement in community-oriented actions. The multivariate logistic regression findings also suggest that community attachment and certain sociodemographic variables (i.e. level of education and length of residence) are significant predictors of community-oriented behaviors. Possible implications of the findings for researchers, public leaders, Cooperative Extension personnel, and community development practitioners are advanced.